2019
DOI: 10.1002/nav.21861
|View full text |Cite
|
Sign up to set email alerts
|

How to deal with consumers who group to request a discount?

Abstract: We investigate operations impacts of consumer‐initiated group buying (CGB), whereby consumers voluntarily form buying groups to negotiate bulk deals with retailers. This differs from regular purchasing whereby consumers visit retailers individually and pay posted prices. Upon the visit by group consumers, a retailer decides to forgo or satisfy their demand in its entirety. Turned down by a retailer, group consumers continue to visit other retailers. In the case where their group effort fails to conclude a deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For example, they focused on the inertia effect, and suggested some methods to overcome it. Recently, Qiu and Jiang (2019) investigated operations impacts of the group-buying price mechanism in the setting with competitive retailers. They found that retailer competition, group size, and the chance that group consumers switch to individual purchasing upon unsatisfaction were important to how retailers adjust operations to deal with consumer-initiated group buying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, they focused on the inertia effect, and suggested some methods to overcome it. Recently, Qiu and Jiang (2019) investigated operations impacts of the group-buying price mechanism in the setting with competitive retailers. They found that retailer competition, group size, and the chance that group consumers switch to individual purchasing upon unsatisfaction were important to how retailers adjust operations to deal with consumer-initiated group buying.…”
Section: Literature Reviewmentioning
confidence: 99%